PEMANFAATAN BIJI ASAM DAN LIMBAH KERTAS DALAM MEWUJUDKAN BATIK YANG RAMAH LINGKUNGAN - Tiara Dahlia Furqon; Diksi Aisyah Isna; Dina Setiya Rini; Nurul Hamida (Politeknik Negeri Semarang, 2022)
Paper or cardboard waste is a lot of waste generated after plastic waste and food waste. The use of high paper and not matched with sufficient waste treatment causes the creation of a slum environment and is not beautiful to look at. In addition to paper waste which contributes to the amount of waste in Indonesia, the use of wax in the batik process in the long term can have a negative effect on the health of batik. Burning candles produces carbon dioxide which is harmful to the respiratory system. Therefore, the use of paper waste and natural materials in the batik-making process is very necessary for the success of the government's waste-free movement program. In making eco-friendly batik, cardboard or cardboard is needed as a material for making stamps and gutha tamarin and butter as a substitute for wax. The targets of this entrepreneurship program are Youth, PKK Members, and all Indonesian people. The program to be implemented includes preparation for business implementation, production, and marketing. The marketing method is carried out directly by collaborating with souvenir centers, cloth sellers, and student cooperatives and online through e-commerce so that the marketing reach is wider.